Instructional Simulations - Vogel-Walcutt, Jennifer J.; Malone, Naomi; Schatz, Sae (International Guide to Student Achievement, 2013)
Simulations are tools that, when used for instruction, allow learners to practice in a repeatable, focused environment (Aldrich, 2004). Instructional computer-based simulations employ a systematic instructional methodology (e.g., scenario-based training) and accurately represent a problem-solving domain (Oser, Cannon-Bowers, Dwyer, & Miller, 1997). This combination enables learners to practice integration of their skills and to perform under realistic conditions, such as environmental distractions, stress, and time pressure (Beaubien & Baker, 2004). Simulations can be utilized across multiple learning domains, from STEM-focused education to arts and humanities; and for a variety of purposes, such as problem solving or studying phenomena not visible to the human eye (Reigeluth & Schwartz, 1989). Additionally, extensive literature exists examining the use of simulations for education, investigating most levels of instruction (from elementary to adult) and spanning many different instructional strategies (West, Snellen, Tong, & Murray, 1991).